Intergenerational conflicts and resistance of daughters in suburban Turkey - (:unkn) unknown (Emerald Group Publishing Ltd., 2017)
This paper draws in part from data of a larger study on marital lives and divorce of women of various ages and backgrounds residing in metropolitan Turkey. The aim of the overall study has been to understand various factors which have paved the ways leading to divorce and the research method used for the study is based on narrative analysis. An important finding of the study is the control of women’s sexuality which is discussed in this paper with the help of the narratives of three women who are raised by dominant fathers and by subordinated mothers. I argue that gender and generation hierarchies are hidden in the idealized image of family life in low- to middle-income families residing in suburban Turkey. Intergenerational conflicts arise due to three women’s oppression in their young ages by their fathers who have decided upon their marriages to control their sexuality. Yet, as young adults, the three women try to find ways to cope with the control of their sexuality. The analysis of the three women’s narratives reveal their endeavors either to challenge the idealized “virgin bride” norm or to get rid of their unwanted marriages through divorce or separation which can be considered as instances of women’s resistance to patriarchal domination and their search for individuation. How much resistance the three women are able to endeavor is dependent on the aspects of gendered interactions and on the embeddedness of ambivalences in gender role models in the patriarchal gender regime of Turkish society. © 2017 by Emerald Publishing Limited.
Keywords: Control of sexuality; Intergenerational conflicts; Patriarchal domination; Resistance of daughters; Virginity